2022
DOI: 10.1037/fam0000879
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Multiracial Youth Socialization (MY-Soc) Scale among racially diverse multiracial emerging adults.

Abstract: Multiracial children are the largest demographic group in the United States among individuals under the age of 18 (Pew Research Center, 2015), but their developmental processes are understudied. Parents and caregivers play an important role in preparing youth to navigate racialized society by teaching them to understand what it means to be a member of a racial-ethnic group (Hughes et al., 2006). However, this process is more complex in multiracial families, where youth belong to multiple racial-ethnic groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…However, the four racial and ethnic socialization frames used when analyzing monoracial families do not always account for the socialization practices parents engage in with multiracial youth. The Multiracial Youth Socialization (My-Soc) scale defines eight types of socialization specific to multiracial youth (Atkin et al, 2021). These eight types are: Navigating Multiple Heritages Socialization, Multiracial Identity Socialization, Preparation for Monoracism Socialization, Negative Socialization, Colorblind Socialization, Diversity Appreciation Socialization, Race-Conscious Socialization, and Silent Socialization.…”
Section: Racial and Ethnic Socialization In Multiracial Familiesmentioning
confidence: 99%
“…However, the four racial and ethnic socialization frames used when analyzing monoracial families do not always account for the socialization practices parents engage in with multiracial youth. The Multiracial Youth Socialization (My-Soc) scale defines eight types of socialization specific to multiracial youth (Atkin et al, 2021). These eight types are: Navigating Multiple Heritages Socialization, Multiracial Identity Socialization, Preparation for Monoracism Socialization, Negative Socialization, Colorblind Socialization, Diversity Appreciation Socialization, Race-Conscious Socialization, and Silent Socialization.…”
Section: Racial and Ethnic Socialization In Multiracial Familiesmentioning
confidence: 99%
“…Four subscales from the Multiracial Youth Socialization Scale were utilized to assess racial socialization that youth perceived they received from each of their parents (Atkin et al, 2021a ). Although the development of the subscales was informed by interviews with Multiracial college students about their experiences with familial socialization (Atkin et al, 2021b ), these four subscales assess socialization experiences relevant to families of all racial backgrounds.…”
Section: Methodsmentioning
confidence: 99%
“…The validity of the four-subscale structure of the Multiracial Youth Socialization Scale was assessed using confirmatory factory analysis, whereby fit was considered adequate if the comparative fit index (CFI) was close to 0.90, root mean square error of approximation (RMSEA) was close to 0.06, and square root mean squared residual (SRMR) was close to 0.08, recognizing that researchers recommending these values do not support rigid cut-offs (see appendix for supplemental table; Hu & Bentler, 1999 ; Perry et al, 2015 ). The internal reliability of the subscales in the scale development study ranged from 0.74 to 0.94 (Atkin et al, 2021a ). In the current study, reliability scores also ranged from 0.74 to 0.94 for mothers’ socialization and fathers’ socialization (see Table 2 for details).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3The Multiracial Youth Socialization (MY-Soc) Scale (Atkin et al, 2021) was developed based off of the themes identified in this study to address this gap in the literature.…”
mentioning
confidence: 99%